Video streaming server for hidden security camera - Nor Assyakirin Binti Yusof (School of Microelectronics, University Malaysia Perlis, 2015)
Nowadays, more frequent crimes reported in the media of television, among homicides and wars. Forensic experts and police have data that has been recorded in the smartphone memory storage before being handed over to the higher authorities and also journalists also have the information before making coverage. Thus, this project was developed so that all the information recorded is not stored in the storage memory to avoid being stolen or changed by unauthorized persons.